Studies in Mexican Grasshoppers: Four new species of Reyesacris Fontana, Buzzetti & Mariño-Pérez, 2011 (Orthoptera: Acrididae: Ommatolampidinae) - Mariño-Pérez, Ricardo; Sanabria-Urbán, Salomón; Pocco, Martina E.; Foquet, Bert; Song, Hojun (Zootaxa, 2021)
Four new species of Reyesacris Fontana, Buzzetti & Mariño-Pérez, 2011 are described from Southern Mexico (Guerrero and Oaxaca States). Reyesacris zihua sp. nov., R. atoyacensis sp. nov., R. mephaa sp. nov. and R. tika sp. nov. A dichotomous key to species of Reyesacris and distribution map are provided together with an analysis of external and internal male genitalia to place this genus in the subtribe Vilernina within the tribe Ommatolampidini.